The variation of obligatory preposition-article contractions in the interlanguage of adult learners of Portuguese - Brito, Edvan P. (Revista do GEL, 2018)
This study analyzes the sociolinguistic variation of obligatory contractions between the preposition de and the definite articles in the interlanguage of adult learners of Portuguese as foreign language in the United States. Using this variation phenomenon as an example, the main objective of this pilot study is to discuss the feasibility of using speech data from telecollaborative interactions in interlanguage variation studies. The analyzed data come from four audio-recorded teletandem sessions held in 2017 among nine US-based learners of Portuguese and native speakers of this language in Brazil. The quantitative analysis included three linguistic group factors —preceding word category, gender marking, and number marking— and four social group factors —learner gender, native language, immersion experience, and teletandem session. The results showed that only gender marking was selected as a significant factor for the occurrence of contraction. The study concluded that speech data from telecollaborative interactions can be used as one of the tasks in large scale interlanguage variation studies. However, it also cautions researchers to consider some of the major issues regarding selection of variables, learners’ style shifting and stage of acquisition, and technical limitations of this type of interaction.